Thermodynamically stable whilst kinetically labile coordination bonds lead to strong and tough self-healing polymers - Lai, Jian-Cheng; Jia, Xiao-Yong; Wang, Da-Peng; Deng, Yi-Bing; Zheng, Peng; Li, Cheng-Hui; Zuo, Jing-Lin; Bao, Zhenan (Nature communications, 2019)
There is often a trade-off between mechanical properties (modulus and toughness) and dynamic self-healing. Here we report the design and synthesis of a polymer containing thermodynamically stable whilst kinetically labile coordination complex to address this conundrum. The Zn-Hbimcp (Hbimcp = 2,6-bis((imino)methyl)-4-chlorophenol) coordination bond used in this work has a relatively large association constant (2.2 × 10 11 ) but also undergoes fast and reversible intra- and inter-molecular ligand exchange processes. The as-prepared Zn(Hbimcp) 2 -PDMS polymer is highly stretchable (up to 2400% strain) with a high toughness of 29.3 MJ m −3 , and can autonomously self-heal at room temperature. Control experiments showed that the optimal combination of its bond strength and bond dynamics is responsible for the material’s mechanical toughness and self-healing property. This molecular design concept points out a promising direction for the preparation of self-healing polymers with excellent mechanical properties. We further show this type of polymer can be potentially used as energy absorbing material. There is often a trade-off between mechanical properties (modulus and toughness) and dynamic self-healing in materials. Here the authors design and synthesize a polymer containing thermodynamically stable whilst kinetically labile coordination complexes to address this conundrum.